A neoclassical perspective on Switzerland's 1990s stagnation - Yannic Stucki; Jacqueline Thomet (University of Bern, Department of Economics, 2018)
We study Switzerland's 1990s growth weakness through the lens of the business cycle accounting framework by Chari, Kehoe, and McGrattan (2007). Our main result is that weak productivity growth cannot account for the experienced stagnation. Rather, the stagnation is explained by factors that made labor and investment expensive. We show that an increase in labor income taxes and financial frictions are plausible causes. Holding these factors constant, counterfactual real annualized output growth over the 1992Q1-1996Q4 period is 1.93%, compared to a realized growth of 0.35%.
Keywords: E13; E20; E32; E65; 330; Business cycle accounting; housing crises; stagnation; Switzerland